Penggunaan Metode Pembelajaran Role Playing Untuk Meningkatkan Keterampilan Berbicara Siswa Di Kelas Iii Sd Negeri Cidadap - Alvina Damayanti; Riga Zahara Nurani; Hatmat Heris Mahendra (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to describe the planning, implementation, and improving the results of the speaking skills of class III students at Cidadap state Elementary School. This research is a classroom action research. The subjectsnin this study werw class III students at Cidadap State Ele,entary Scool, totaling 28 students consisting of 19 girls and 9 boys. Source of data in this study are qualitative and quantitative data. Data collection using observation instruments, interviews, tes. And dokumentatios. The results showed that the use of the role playing method in class III Cidadap State Elementary School could improve the speaking skills of class III Cidadap State Elementary School could improve the speaking skills og class III students. This study consisted of 2 cycles. In sycle I the average score of students was 72.32 with a total number of students who completed as many as 10 students (35.7%) , in sycle II the average score of students increased to 83.5 with the number of students who completed as many as 25 people (89,5%). In the learning precess, the use of the role playing method can improve students speaking skills in class III Cidada State Elementary School.